The Influence of Music on Mood in Students - Najhan Haque; Djannatun Ni’mah Dwi Astuti; Tiara, Tiara Fatima Syahrani (CV. Era Digital Nusantara, 2024)
Music has a strong influence on human moods and emotions, it is said that music can stimulate feelings of happiness, sadness, relaxation, and even to increase energy. This study was conducted to determine whether music with a certain volume can affect a person's mood comfort either when given a stimulus of happy music or sad music. This type of research is experimental research which uses a single subject research model with 30 subjects, each subject is given a different stimulus with the same treatment and there is a control group that gets an experiment to hear songs that express sad and happy emotions, and vice versa with the experimental group.